Bis[(4-chlorobenzyl)triphenylphosphonium] tetra-chloridozincate(II) trihydrate - Tan, Kong Wai; Ng, S.W.; Maah, Mohd Jamil (International Union of Crystallography, 2010)
The crystal structure of the title compound, (C 25H 21ClP) 2-[ZnCl 4]·3H 2O, consists of tetra-hedral phosphonium cations and tetra-hedral zincate anions; the water mol-ecules form weak hydrogen bonds to the anions. Two of the water mol-ecules are disordered over three sites in a 0.68:0.55:0.77 ratio.